Moving (too) fast? Addressing temporality and acceleration in Portuguese business ventures scaling. - Coelho, J. V. (15th ESA Conference, 2021)
Economic action is increasingly taking place in temporary settings and systems. Temporality regimes and acceleration, i.e., the performance of activities in ever-shorter periods of time, have distinctive importance as contemporary underlying sociocultural framework, primarily contributing to the socioeconomic base of a business venture. Although prior research has highlighted that temporality and time regulation as key dimension to drive business ventures creation and scaling, little is known on speeding-up implications, namely on how actors experience speed as infrastructural base of employment relations. Analytical work is based on a 12-month ethnographic study carried out in one of the most successful start-up ventures operating in Portugal, aimed to explore how actors experience their startupper employment relations. Analysis shows that speeding-up involve a plurality of partly conflicting implications, and such conflicts invoke tensions that actors live out in their daily activities. Three relational attributes are discussed as speeding-up implications, in an employment relations perspective: the prevalence of a short-termed task focus, emerging speed as a reassuring proxy for success and accomplishment; low levels of trust and institutionalized reciprocity; short-lived social relations and conflict deprioritisation. The study has implications for understanding temporality and time uses in the expanding literature on contemporary economic action, namely in emergent contexts such as the Portuguese.